Dense breast as a risk factor in breast malignancy - Khalil, Saabh Ismail; Khalel, Enam A.; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: One of the strongest risk factors for breast cancer is high breast density, relatively little fat in the breast and more connective and glandular tissue.Objectives: this study aims to measure risk of increase breast density in correlation of CA breast & compare our results with results in other population, to compare the performance of ultrasonography and mammography in measuring breast density according to BIRDS systemMaterials &methods: The study included 45 females .Measuring risk of increase breast density in correlation of CA breast & comparing the performance of ultrasonography and mammography in measuring breast density according to BIRADS system.Results : there is strong influence of breast density as a risk factor of breast CA, according to mammography, it had been significantly found that mammographic density was the more prevalent among CA patients it found in According to mammography, also use of RI as significant and important way for estimation of density as use of 0.6 as a cutoff point, as 91% of dense breast had RI more than 0.6.Conclusions : increase breast density is associated with possible increase risk of CA breast and use of ultrasound, mammogram and RI play a role in estimating breast density.